Emotional Communication in Finger Braille - Yasuhiro Matsuda; Ichiro Sakuma; Yasuhiko Jimbo; Etsuko Kobayashi; Tatsuhiko Arafune; Tsuneshi Isomura (Advances in Human-Computer Interaction)
We describe analyses of the features of emotions (neutral, joy, sadness, and anger) expressed by Finger Braille interpreters and subsequently examine the effectiveness of emotional expression and emotional communication between people unskilled in Finger Braille. The goal is to develop a Finger Braille system to teach emotional expression and a system to recognize emotion. The results indicate the following features of emotional expression by interpreters. The durations of the code of joy were significantly shorter than the durations of the other emotions, the durations of the code of sadness were significantly longer, and the finger loads of anger were significantly larger. The features of emotional expression by unskilled subjects were very similar to those of the interpreters, and the coincidence ratio of emotional communication was 75.1%. Therefore, it was confirmed that people unskilled in Finger Braille can express and communicate emotions using this communication medium.